The effect of atmospheric pressure plasma treatment on wetting and absorbance properties of cotton fabric. (2021) - Sandanuwan, Thisara; Hendeniya, Nayanathara; Amarasinghe, D.A.S.; Attygalle, Dinesh; Weragoda, Sampath
Abstract: In textile dyeing and printing, fabric wettability plays a major role for good surface finish. Woven cotton fabrics contains starch, accumulated from sizing agents used for yarns which needs to be removed before coloration and finishing processes. The conventional method of removing the starch and making the cotton fabric ready for further steps is a wet chemical treatment that uses desizing, scouring, and bleaching agents in the process which has drawbacks of consumption of large amount of water and energy and pollution from effluents. The need for an environmentally friendly, cost-effective, and energy-efficient desizing method is in the interest of the industry. During this study, the effect of atmospheric pressure plasma treatment on the enhancement of wettability and dyeing properties of cotton fabric was studied.